Pharmaceutical care issues identified by pharmacists in patients with diabetes, hypertension or hyperlipidaemia in primary care settings - Chua, Siew Siang; Kok, L.C.; Yusof, F.A.; Tang, G.H.; Lee, S.W.; Efendie, B.; Paraidathathu, T. (BMC, 2012)
BACKGROUND: The roles of pharmacists have evolved from product oriented, dispensing of medications to more patient-focused services such as the provision of pharmaceutical care. Such pharmacy service is also becoming more widely practised in Malaysia but is not well documented. Therefore, this study is warranted to fill this information gap by identifying the types of pharmaceutical care issues (PCIs) encountered by primary care patients with diabetes mellitus, hypertension or hyperlipidaemia in Malaysia. METHODS: This study was part of a large controlled trial that evaluated the outcomes of multiprofessional collaboration which involved medical general practitioners, pharmacists, dietitians and nurses in managing diabetes mellitus, hypertension and hyperlipidaemia in primary care settings. A total of 477 patients were recruited by 44 general practitioners in the Klang Valley. These patients were counselled by the various healthcare professionals and followed-up for 6 months. RESULTS: Of the 477 participants, 53.7 had at least one PCI, with a total of 706 PCIs. These included drug-use problems (33.3), insufficient awareness and knowledge about disease condition and medication (20.4), adverse drug reactions (15.6), therapeutic failure (13.9), drug-choice problems (9.5) and dosing problems (3.4). Non-adherence to medications topped the list of drug-use problems, followed by incorrect administration of medications. More than half of the PCIs (52) were classified as probably clinically insignificant, 38.9 with minimal clinical significance, 8.9 as definitely clinically significant and could cause patient harm while one issue (0.2) was classified as life threatening. The main causes of PCIs were deterioration of disease state which led to failure of therapy, and also presentation of new symptoms or indications. Of the 338 PCIs where changes were recommended by the pharmacist, 87.3 were carried out as recommended. CONCLUSIONS: This study demonstrates the importance of pharmacists working in collaboration with other healthcare providers especially the medical doctors in identifying and resolving pharmaceutical care issues to provide optimal care for patients with chronic diseases.